1998
DOI: 10.1159/000023925
|View full text |Cite
|
Sign up to set email alerts
|

IL-8 and the Activation of Eosinophils and Neutrophils following Nasal Allergen Challenge

Abstract: Background: A growing body of evidence suggests that proinflammatory cytokines play a role in allergic inflammation by attracting and activating inflammatory cells. In this study, we have investigated the relationship between interleukin-8 (IL-8) in nasal lavage fluid and the local activation of eosinophils and neutrophils following nasal allergen challenge of allergic patients. Methods: Nasal challenges were performed with grass pollen extract in 14 allergic patients and 5 nonallergic controls. Nasal lavage f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 31 publications
2
14
0
Order By: Relevance
“…The increase in nasal IL-5 and IL-8 and the subsequent influx of inflammatory cells accompanied by the increase in the soluble cell markers ECP and MPO as found in this study is in agreement with the results of other studies [12, 14, 23, 32, 33, 34, 35]. The association between increases in the chemoattractants IL-5 and IL-8 and the nasal influx of eosinophils and neutrophils, respectively, during the late phase, is in agreement with their reported role for the recruitment of these inflammatory cells.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…The increase in nasal IL-5 and IL-8 and the subsequent influx of inflammatory cells accompanied by the increase in the soluble cell markers ECP and MPO as found in this study is in agreement with the results of other studies [12, 14, 23, 32, 33, 34, 35]. The association between increases in the chemoattractants IL-5 and IL-8 and the nasal influx of eosinophils and neutrophils, respectively, during the late phase, is in agreement with their reported role for the recruitment of these inflammatory cells.…”
Section: Discussionsupporting
confidence: 94%
“…Primary outcomes were levels of interleukin-5 (IL-5), IL-8, eosinophil cationic protein (ECP), myeloperoxidase (MPO) and cell differentials obtained during the phase of the late allergic reaction (4–24 h). Early protein leakage (α 2 -macroglobulin, A2M) and histamine levels were monitored as an indicator for early mast cell degranulation in the nose [12, 13, 14, 15]. The study was designed to detect a 25% difference in late skin reactivity and a 30% difference in log-normalized levels of soluble markers with a power of 0.80 and a 95% confidence level.…”
Section: Introductionmentioning
confidence: 99%
“…43,44 An increase in IL-5, IL-8, eotaxin, and ECP levels was generally reported. 43,[45][46][47][48][49] A few studies only indicated an inhibition of IL-8 secretion by astemizole in a nasal challenge with allergen and of ECP and eosinophil influx by cetirizine, loratadine, or azelastine in seasonal trials. [50][51][52][53] In this single-dose trial, we could not demonstrate any effect of either levocetirizine or desloratadine at 5 mg on cytokine levels (IL-4 and IL-5), on chemokine levels (IL-8 and eotaxin), or on ECP secretion.…”
Section: Discussionmentioning
confidence: 99%
“…31 32 In our study, the absence of ECP increase after antigen challenge may be due to late phase release (more than six hours later) of this mediator during hypersensitivity reactions, as has been shown in faeces, tears, and nasal and bronchial fluids 2931 33-35 In contrast, non-atopic patients with intolerance to milk or patients with coeliac disease exhibited early increases in intestinal ECP release (20 minutes) after intraluminal antigen provocation 2736 However, the degranulation of eosinophils in these cases may have involved mechanisms other than IgE mediated hypersensitivity, such as IgA or IgG antibodies, which are also potent activating stimuli for the release of ECP 37…”
Section: Discussionmentioning
confidence: 99%